Análise de expressão dos genes de controle do ciclo celular e fuso mitótico como possíveis biomarcadores de resposta ao tratamento com eritropoetina em pacientes com síndrome mielodisplásica - Andrade, Cinthya Cavalcante (2018)
The myelodysplastic syndromes (MDS) are heterogeneous clonal diseases that are associated with cytopenias in peripheral blood, ineffective hematopoiesis, bone marrow hyperplastic disease with morphologically defined dysplasia in one or more lineages in addition to increased risk of progression to acute myeloid leukemia (AML). Treatment with erythroid stimulatory agents, such as erythropoietin (EPO), is considered the first line in most MDS anemias. It has been shown that changes in the expression of proteins related to the mitotic spindle (AURORA A, AURORA B and TPX2), mitotic checkpoint (CDC20 and MAD2) and cell cycle regulator genes (CDKN1A) are involved in chromosomal instability and aneuploidies in several tumors. This study aims to evaluate the expression profile of these genes and its association with laboratory clinical variables, regarding the response to the treatment with of patients with MDS, in order to identify new possible biomarkers of response to the treatment. Gene expression analysis was performed (Real Time-PCR) based on data from the gene expression database of the Cancer Cytogenomics laboratory from 43 MDS patients who used EPO. Initially, it was identified that the expression of the AURKA (p = 0.013) and AURKB (p = 0.021) were increased in patients who responded to EPO treatment when compared to patients who did not respond. Afterwards, to evaluate the expression profile, the Cuttof Finder software was used to define cutoff points and stratification of patients regarding the response to EPO treatment. Based on the waterfall plot graph, the AURKA (p = 0.023, OR = 4.0) and AURKB (p = 0.02; OR = 6.5) genes were found to have an important association between their gene expression profile and response to EPO treatment. From these analyses, the patients were stratified in face of the increase / decrease of their expression and regarding the responsiveness or not to the treatment with EPO. in the assessment through the chi-square test, followed by multinomial logistic regression analysis, it was found that the increase in expression of AURKA (OR = 4,000, p = 0.064) and AURKB (OR = 6,500; p = 0.027) were associated with an increase in the patient's chances of responding to EPO. As for the evaluation of the clinical-laboratory variables, for the AURKA gene, it was observed that the increase in its expression is associated with an increased chance of the patient having a peripheral cytopenia (OR = 4.889, p = 0.037), normal karyotype = 1.114, p = 0.028), does not be transfusional dependent (OR = 4.533, p = 0.031). For the other genes (MAD2, TPX2, CDC20 and CKN1A, no significant associations were found between expression profile and response to treatment (p> 0.05). These results suggest that AURKA and AURKB can be considered as possible markers of response to treatment with Erythropoietin in patients with MDS.